The Effect Of Fintech, Number Of Directors, Profitability, GDP And Bank Size On Banking Stability Listed On The Indonesia Stock Exchange In 2018-2021 - Khoirunisa Khoirunisa; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This research was conducted with the aim of finding out the effect of fintech, number of directors, profitability, GDP and bank size on the stability of banks listed on the IDX using a modified Altman Z- Score formula. The sample in this study is 40 banks in Indonesia for the 2018-2021 period. The method used in this study is a quantitative approach and panel data regression analysis and uses REM as the best model after passing the Hausman Test. The results of the study show that together or simultaneously there is a significant influence from fintech, number of directors, profitability, gross domestic product (GDP) and bank size on banking stability and segmentally or partially there are 2 variables that have a positive influence on banking stability namely fintech (X1) with the results of t count > t table, namely 4.480633 > 1.975092073 and gross domestic product (GDP) (X4)with the results of t count > t table, namely 2.236197 > 1.975092073. While the other three variables partially have a negative effect on bankingstability, namely the number of directors (X2) with the results of t count < t table, namely 0.687293 < 1.975092073, profitability (X3) with the resultsof t count < t table, namely 1.432645 < 1 .975092073 and bank size (X5) with the results of t count < t table, namely 0.600556 < 1.975092073.